Ecological discourse and environmental education in English textbooks: a multimodal eco-critical discourse analysis - Triyono, Sulis; Sahayu, Wening; Margana; Fath, Sahnaz Natasya (Penerbit Universiti Kebangsaan Malaysia, 2023)
While ecolinguisticsstudies in revealing ecological discourse have been appealed to and executed by several scholars, the eco-critical discourse analysis combining text and visual analysis of ecological discourse in textbooks seems largely unexplored. In response to the gap, this study aims to uncover text and visual-ecological discourse and inquire about the environmental education in English as a Foreign Language (EFL) textbook utilised in Indonesian senior high schools (SHSs). The textual discourses were categorised and coded based on the mood ecological element system and justified by the ecological concept. Similarly, visual illustration was analysed and categorised by ecosophy judgment. The ecological text and task were examined critically to decide the environmental education presented in the textbook. The result indicates that eco-beneficial discourse is demonstrated chiefly, while only a few eco ambivalent and eco-destructive discourses are presented. The visual discourses likely exhibit a similar propensity to portray more eco-beneficial illustrations. The finding also unveils that only a small proportion of the highest environmental skills are embedded, mainly catering for the lowest level of environmental education skills. Therefore, stakeholders, including curriculum developers, book authors, and English teachers, are advised to be more aware of and incorporate environmental education and its concepts into their teaching practices.